ChemInform Abstract: Efficient Methods for the Synthesis of α‐Aminophosphonate Fluoroalkyl Esters. Issue 26 (6th June 2013) - Skorenski, Marcin; Oleksyszyn, Jozef; Sienczyk, Marcin
Abstract Two similar one‐pot procedures are presented for the synthesis of title compounds (IV).